History of Psychotherapy in Slovakia - Morovicsová, Eva; Heretik Sr., Anton; Heretik Jr., Anton; Škodáček, Igor (European Journal of Mental Health, 2017)
Authors present the history of psychotherapy in Slovakia. The first section refers to the social requirements for psychology and psychotherapy development. The history of psychotherapy alone is analysed in three stages of development. The first stage includes the years 1918–1945, where, related to the activities of the Clinic of Psychiatry and Neurology of the Faculty of Medicine of Comenius University in Bratislava, we come across the first attempts at applying psychotherapeutic approaches in medical practice and in the training of physicians. The second developmental stage (1945–1989) introduces individuals that significantly influenced the development of psychotherapeutic theories and their application in individual fields of clinical practice. They simultaneously show the contribution of the training school SUR to the development of psychotherapy in Slovakia. The most significant changes in the aspect of domestication and development of psychotherapy in Slovakia happened in the last characterised stage, in the period following the Velvet Revolution in 1989. The previously almost unavailable psychotherapeutic literature became available and psychotherapy was gradually introduced into the undergraduate and postgraduate education of physicians and other professionals. The first Slovak Society of Psychotherapy was founded and became a common ground for professionals in this field. In the final section of this paper, the authors present current questions and problems of the development, research and application of psychotherapy in Slovakia and briefly characterise the influence of legislation changes and reforms in healthcare on the position of psychotherapy.